2011
DOI: 10.1161/strokeaha.110.601799
|View full text |Cite
|
Sign up to set email alerts
|

Burden of Stroke in Indigenous Western Australians

Abstract: Background and Purpose-Despite the disproportionate burden of cardiovascular disease among indigenous Australians, information on stroke is sparse. This article documents the incidence and burden of stroke (in disability-adjusted life years) in indigenous and non-indigenous people in Western Australia (1997)(1998)(1999)(2000)(2001)(2002), a state resident to 15% of indigenous Australians comprising 3.4% of the population of Western Australia. Methods-Indigenous and non-indigenous stroke incidence and excess mo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

10
71
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 67 publications
(81 citation statements)
references
References 24 publications
10
71
0
Order By: Relevance
“…It has been previously reported that Indigenous Australians face a disproportionate burden of stroke [9]. Data show that the ageadjusted incidence rate of stroke in Indigenous people is approximately three-times that of other Australians [9].…”
Section: Introductionmentioning
confidence: 98%
See 2 more Smart Citations
“…It has been previously reported that Indigenous Australians face a disproportionate burden of stroke [9]. Data show that the ageadjusted incidence rate of stroke in Indigenous people is approximately three-times that of other Australians [9].…”
Section: Introductionmentioning
confidence: 98%
“…Data show that the ageadjusted incidence rate of stroke in Indigenous people is approximately three-times that of other Australians [9]. National hospitalisation rates for stroke are subsequently two-times greater and associated with a reduced quality of inpatient care and outcomes [9,10].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…They also have ongoing issues related to social isolation, lack of employment prospects, reduced ability to engage in everyday activities and significant family disruption [2]. While data are available on incidence, mortality and risk factors for stroke in Aboriginal Australians [3][4][5], relatively little information is available on functional consequences in this group. Exceptions to this lack of information include an article related to the stories of three Aboriginal men with aphasia after stroke [6].…”
Section: Introductionmentioning
confidence: 99%
“…However, given the paucity of reliable data in this area, these data provide the best available evidence and the disparities in stroke burden reported in this issue of Stroke are alarming enough. 3 The excess risk of stroke in Indigenous Australians originates from a number of different factors. 8 These factors include those originating from relative social, economic, and educational disadvantage, those associated with physiological factors such as from intergenerational changes, 9 as well as those arising from psychological factors.…”
mentioning
confidence: 99%